“Once upon a time in Bronx” and the current urban challenges of the Theater of the Oppressed. Combination of participatory art and theater in public spaces in Bronx, New York City, USA - Lima e Ferreira, Ana Carolina (Urban, 2016)
Introduction The Theater of the Oppressed is a method to empower the oppressed to fight against their oppressors by developing plays. It is very widespread around the world. The main idea of this theater method is to fight against basically all kinds of oppressions. As the Theater of the Oppressed is reflecting the left wing ideas from the 70s, it was received with skepticism in 90s in the USA but later gained the trust of the New Yorkers. The artist Melanie Crean goes beyond using the Theater of the Oppressed blended in two consistent art projects and showing that this method can be used as a media of art in public spaces. Keywords Storytelling; Theater of the Oppressed; art in public spaces and urban transformation